Meningkatkan Hasil Belajar IPA Melalui Penerapan Metode Belajar Inkuiri Siswa Kelas 4 SDN Babakan Bandung Kota Sukabumi - Imas Mulyaningsih (FKIP Universitas Muhammadiyah Sukabumi, 2019)
This research based on unoptimal gain of fourth grade elementary school students average score in science, which is the 65 point of minimum score couldn’t be reach by the students, especially in subject function of plant’s parts. Conventional learning approach has conclude as one of many indicator that the students learning activity have not improve better and it cause learning result become unoptimal. The aims of the research are; 1) to describe science learning plan using inquiry method, 2) to describe science learning activities using using inquiry method, 3) to describe student learning result improvement using inquiry method for science subject. This research approach is Classroom Action Research has adopted Kemmis & McTaggart method through 3 (three) cycles of learning. The subjects of the research are 40 students of 4th grade Babakan Bandung Elementary School. The research conludes of 1st cycle that is students score average just reach 54.86. On 2nd cycle has rised to 69.46, then on 3rd cycle has rised significantly to 80.54. According to the score average result, inquiry Method implementation has able to improve the students score of science optimally.